Edificio Paraninfo. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2023)
Rodrigo Arias Camacho, Miguel Ángel Rodríguez Echeverría, Lorena Clare Facio.
Colección Fototeca UNED
Keywords: UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; Rodríguez Echeverría, Miguel Ángel -- Presidente de la República -- 1998-2002; Arias Camacho, Rodrigo, Rector -- Rector -- 1999-2009; 2019-2024;2024-2029; Clare Facio, Lorena; FOTOTECA